Struktur Lapisan Sosial & Potensi Pemuda dalam Mendorong Pembangunan Desa Wisata di Yogyakarta - Sri Anom Amongjati; Sayyid Al Bahr Maulana; Sofyan Sjaf (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The status of Wukirsari Village as a tourist village has not been able to overcome social and economic inequality between levels of society, thus giving rise to the need for a more inclusive development strategy. With cultural, ecological, and historical advantages and its status as a Tourist Village, it does not guarantee that the impact of development is felt evenly by the community. The quantitative approach in this study shows that 16% of families are in the lower class with differences in terms of economic expenditure, access to training, and economic skills that are quite significant with the upper class. Likewise, the Gini Index with a score of 0.409 indicates moderate inequality in terms of expenditure distribution. Solutions are needed to reduce inequality and equalize development, one of which is to encourage the role of youth in village development. With the potential of youth who are good at leadership participation and health-welfare, supported by increased education, it is hoped that youth can become agents of change in society in supporting development. This study shows the economic characteristics of each level of society, the inequality they experience and emphasizes the importance of the strategic role of youth in reducing inequality through increased capacity, active participation in development, and support for inclusive village policies.